IMPLEMENTING SPEED READING STRATEGY IN INCREASING STUDENTS’ READING COMPREHENSION AT DAARUL HUFADZ ISLAMIC BOARDING SCOOL PADANG - Vivi Zurniati; Indri Astuti; Kristian Burhan; Teti Indrayani; Nofriza Efendi; Rezi Junialdi (PEDAMAS (PENGABDIAN KEPADA MASYARAKAT), 2024)
English at Islamic Boarding School can be challenging since limitation and differences among all subjects in the curriculum. The bias status of being neglected and minor attention compared to Islamic subjects, moral and ethical to school discipline has made ELT should be required the limitation and burden to adapt and customize. To answer that challenge, particular strategies should be made to overcome this problem. Daarul Hufadz Islamic Boarding School as one of Islamic Boarding Schools set their last year students in Junior and Senior High level follow the final semester examination along with regular school students. Therefore, teaching English should meet the set-up. This Community Service tried to see the effect of implementing Speed Reading Strategy to make teaching English more effective and efficient and enable the teacher to get inspiration and information about strategy in classroom. The method used in this Community Service was the quasy-experimental study activity assistance by giving teaching treatment. The result of it is that the Speed Reading Strategy gives significant effect towards the students’ reading comprehension. The prior average score was 70 and after giving the strategy the average was 80. Therefore, it is hoped that English teacher with the same circumstances, learning atmosphere, and learning outcomes can get information and inspiration to teach English so that it can meet the challenging yet it is one of the ways out.